NIKAH SIRRI MENENTANG PUBLISITAS PERKAWINAN - Muhammad Amir Langko (Al-Bayyinah, 2017)
AbstractThis writing is to explain the importance of publication in marriage. The aim is ti anticipate the society misperception about relation of husband and wife and to strengthen not neglected or lost. In sirri marriage the aspect of publication is neglected on purpose. Based on the study done, in fact, it is found that there are a difference and similarities between sirri marriage in the concept of fig and the reality found in Indonesian society. The defense is clearly sen on the regulation of marriage recording, while the similarity lies on the aspect of keeping secret from other people and the negative impact which arises as the result of keeping secret the marriage.Kata Kunci: Nikah Sirri, Perkawinan